Легенда о земном рае (Библиосфера)
In the scientific circulation the text is introduced, that earlier has not attracted researchers' attention - the XVI century treatment of the episode from the Epistles of the Earth paradise by Novgorod Archbishop Vassilij Calica on Novgorod people, who found the paradise on the Earth. The author makes an attempt, basing on indirect evidence to date the creation of the text presented. The text of the legend about Novgorod sailors is given in the Appendix.